Grammatical meaning of the prefix ber- in the Gurindam Dua Belas by Raja Ali Haji (Morphological study) - Sukma, Sukma; Nasution, Khairina; Deliana, Deliana; Widayati, Dwi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research aims to find out the grammatical meaning of the prefix ber- in Gurindam Dua Belas by Raja Ali Haji. This research is library research using a qualitative approach. The data in this research is the forms of the prefix ber- contained in the text Gurindam Dua Belas by Raja Ali Haji. The data collection techniques used are listening techniques and note-taking techniques. This research uses Ramlan's structural morphology theory which then analyzes the data using the agih method with the expansion technique to determine the grammatical meaning of the prefix ber-. The results of the research are that there are 18 words that use the prefix ber- in Gurindam Dua Belas by Raja Ali with the allomorph forms ber- and bel-. The grammatical meaning of the prefix ber found in the context of sentences in Gurindam Dua Belas can be interpreted literally or is still continuous with its lexical meaning such as the words bertiang, bersungguh-sungguh, berjalan, berbuat, berbahagia, berilmu, bertanya, belajar, berakal, bercampur, berkata-kata, berguru, berseteru, berjasa, and beroleh. Apart from that, the prefix ber- was also found which has a figurative meaning, causing implied meanings to emerge, such as in the words bertanah and berkuda. Lastly, the use of the prefix ber- in classical Malay was discovered so that if it was not related to the context, the word could have a different meaning today, such as the word berperi.